Characterization of Patients with Embolic Strokes of Undetermined Source in the NAVIGATE ESUS Randomized Trial - Kasner, Scott Eric; Lavados, Pablo; Sharma, Mukul; Wang, Yongjun; Wang, Yilong; Dávalos, Antoni; Shamalov, Nikolay; Cunha, Luis; Lindgren, Arne; Mikulik, Robert; Arauz, Antonio; Lang, Wilfried; et al. (Journal of stroke and cerebrovascular diseases, 2018)
BACKGROUND: The New Approach Rivaroxaban Inhibition of Factor Xa in a Global Trial vs. ASA to Prevent Embolism in Embolic Stroke of Undetermined Source (NAVIGATE-ESUS) trial is a randomized phase-III trial comparing rivaroxaban versus aspirin in patients with recent ESUS. AIMS: We aimed to describe the baseline characteristics of this large ESUS cohort to explore relationships among key subgroups. METHODS: We enrolled 7213 patients at 459 sites in 31 countries. Prespecified subgroups for primary safety and efficacy analyses included age, sex, race, global region, stroke or transient ischemic attack prior to qualifying event, time to randomization, hypertension, and diabetes mellitus. RESULTS: Mean age was 66.9 ± 9.8 years; 24% were under 60 years. Older patients had more hypertension, coronary disease, and cancer. Strokes in older subjects were more frequently cortical and accompanied by radiographic evidence of prior infarction. Women comprised 38% of participants and were older than men. Patients from East Asia were oldest whereas those from Latin America were youngest. Patients in the Americas more frequently were on aspirin prior to the qualifying stroke. Acute cortical infarction was more common in the United States, Canada, and Western Europe, whereas prior radiographic infarctions were most common in East Asia. Approximately forty-five percent of subjects were enrolled within 30 days of the qualifying stroke, with earliest enrollments in Asia and Eastern Europe. CONCLUSIONS: NAVIGATE-ESUS is the largest randomized trial comparing antithrombotic strategies for secondary stroke prevention in patients with ESUS. The study population encompasses a broad array of patients across multiple continents and these subgroups provide ample opportunities for future research.
Keywords: Platelet Aggregation Inhibitors; Comorbidity; Age Factors; rasové skupiny; Sex Factors; mužské pohlaví; Male; senioři; senioři nad 80 let; výsledek terapie; cévní mozková příhoda; Female; Humans; Ischemic Attack, Transient; rivaroxaban; tranzitorní ischemická ataka; lidé; Fibrinolytic Agents; Middle Aged; ženské pohlaví; lidé středního věku; Racial Groups; Rivaroxaban; inhibitory faktoru Xa; intrakraniální embolie; Intracranial Embolism; rizikové faktory; Stroke; Aged, 80 and over; Factor Xa Inhibitors; komorbidita; inhibitory agregace trombocytů; sexuální faktory; Double-Blind Method; Treatment Outcome; fibrinolytika; Risk Factors; Aspirin; Aged; věkové faktory; dvojitá slepá metoda